Analisis Perbandingan Sistem Pajak Bumi Dan Bangunan (PBB) Di Negara Indonesia Dan Malaysia - Farika, Divha Adhania; Dompak, Timbul; Salsabila, Lubna (LPPM Universitas Putera Batam, 2024)
This research analyzes the comparison of the existing land and building tax systems in Indonesia and Malaysia. The purpose of this article is to discuss what can be used as a comparison regarding the existing land and building tax systems in Indonesia and Malaysia. Land and building tax (PBB) is a potential source of revenue for Indonesia and Malaysia. Apart from that, this journal discusses regional taxes, as well as discussing factors in society that have minimal awareness of paying taxes, especially Land and Building Tax. This journal uses qualitative analytical research because it aims to investigate or describe comparisons of the land and building tax systems of Indonesia and Malaysia. PBB or Land and Building Tax is a Regional Tax which is a regional income system, one of which is regional income from PBB, income from PBB is used to stabilize regional autonomy so that it becomes broad, real and responsible. The results and discussions written in this journal discuss the differences or similarities regarding Land and Building Tax, not only that but there is also a discussion regarding where the tax calculations are obtained. The conclusion is that PBB in Indonesia and Malaysia is different, starting from the subject, objects, rates, management and payment methods.